Analysis of Financial Performance Using Du Pont System Approach - Moh MF Ginda Male; Lanto Miriatin Amali; Meriyana Fransisca Dungga (Universitas Negeri Gorontalo, 2019)
The research was conducted to be used as an evaluation of financial performance using analysis measurement of Du Pont System with quantitative descriptive approach. The analysis was more thorough and it could identify how strong of relationship of profit margin, asset turnover, use of debt and ROI on ROE at textile and garment industry company listed in IDX during 2015-2017 periods which encompassed PT Argo Pantes Tbk, PT Century Textile Industry Tbk, PT Eratex Djaja Tbk, PT Ever Shine Textile Industry Tbk, PT Panasia Indo Resources Tbk, PT Asia Pasific Investama Tbk, PT Asia Pasific Fibers Tbk, and PT Sri Rejeki Isman Tbk by using Du Pont System analysis, with variabels of NPM, TATO, ROI and ROE. The finding of research showed that ROE and ROI at textile and garment industry listed in IDX for 2015-2017 periods was less good due to only 3 companies out of 8 which had very good result of ROI and ROE which were PT. Eratex Djaja Tbk, PT Sri Rejeki Isman Tbk and PT Asia Pasific Investama Tbk and it meant the financial performance was good. Meanwhile the rest 5 companies always showed negative value and result of ROI and ROE was less good with one company for being the lowest namely PT Panasia Indoe Resources Tbk which showed the value of ROI and ROE that was prone to decline year by year.